2004
DOI: 10.3201/eid1010.040147
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and Temporal Trends in Influenzalike Illness, Japan, 1992–1999

Abstract: Kriging analysis improved visualization and understanding of trends in seasonal ILI activity in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 16 publications
3
65
2
Order By: Relevance
“…), and the latter [10] pointed to major traffic pathways and local contact networks. Prevailing westerlies appear to play an important role in the case of Japan, which was noted by Sakai et al [13]. The data used in that study were cases reported from 1992 to 1999, and the Kriging method was used for analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…), and the latter [10] pointed to major traffic pathways and local contact networks. Prevailing westerlies appear to play an important role in the case of Japan, which was noted by Sakai et al [13]. The data used in that study were cases reported from 1992 to 1999, and the Kriging method was used for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to identify such regularities through quantitative analysis, and then to investigate the causes of these regularities. To date, spatiotemporal analyses of influenza epidemics have been performed in France [3,4], Scotland [5], 20 European countries [6], Australia [4], Brazil [7], the United States [4,[8][9][10][11], China [12], and Japan [13,14]. These studies identified several regularities in influenza epidemics: west-to-east spread of peak influenza activity, spatiotemporal epidemic synchrony, close correlation with movement of people, relation with mortality pattern, and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Valuable information concerning epidemics, such as spatial variations, dynamics and periodicity, cannot be derived from the generally short historic records by this definition. Sakai et al [9] slightly modified this approach by identifying the annual maximum of the smoothed data. They incorporated information from weeks before and after the peak event by smoothing data with a five-week unweighted moving average of weekly reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…According to the semivariogram model, kriging methods estimate the value at an unsampled location using values of adjacent samples and distances from the unsampled location to these samples. Kriging methods have been used in many healthrelated studies (Walter, 1994;Diggle et al, 1998;Klienschmidt et al, 2000;Sakai et al, 2004). Ordinary kriging is used in this study to model the spatially dependent local variation in the residuals.…”
Section: Kriging Modelsmentioning
confidence: 99%